Synthesis and Characterisation of Metallosurfactants as Carbon Dioxide Viscosity Modifier - Mohamed, Azmi; Abdosalam, Khadega R (EDUCATUM Journal of Science, Mathematics and Technology, 2017)
This paper focuses on a systematic approach to enhance the viscosity of supercritical CO2 (scCO2) for enhanced recovery applications. Recent successful results have shown for the first time that fluorinated surfactants can be used as viscosity modifiers for CO2. Although some fluorinated surfactants have been synthesised, up to now no systematic studies have been carried out toward scCO2 viscosity enhancement and impeded commercial developments of viscosity modifier. Here, metallosurfactant structure design was focused on anionic surfactant analogues of Aerosol -OT (sodium bis (2-ethyexyl) sulfosuccinate). The metallosurfactant were systematically synthesised with modification centred on fluorinated content in surfactant chain with introduction of nickel (Ni2+) and manganese (Co2+) counter ions. The metallosurfactant have been investigated by a range of techniques including Nuclear Magnetic Resonance (NMR) Spectroscopy, UV-Visible Spectroscopy and High-Pressure Viscometer. The result shows that fluorination is a crucial factor influencing Aerosol-OT surfactant analogue compatibility with scCO2. The presence of fluorine in the metallosurfactant chemical structure gives rise to relative scCO2 viscosity. The results obtained are beneficial for expanding CO2 in enhanced oil recovery applications and realising its potential using the most efficient metallosurfactant as CO2 viscosity modifier.